THE IMPLICATIONS OF THE USE OF ENGLISH AS A LINGUAL FRANCA ON THE LINGUISTIC CHANGES OF THE COLLOQUIAL DIALECTS OF ARABIC - Omar, Abdulfattah A. (Cadernos de Linguagem e Sociedade, 2018)
With the development of globalization and the emergence of global English, numerous studies have been concerned with the ways Arabic is influenced by English, the adoption of many English loanwords by Arab speakers and the dominance of English as a lingua franca in different Arab countries including Saudi Arabia. These studies generally investigate the effects of global English on the Arab linguistic and cultural identity. The majority of these studies tend to list what they refer to as risks of the dominance of English loanwords in Arabic and assert the importance of keeping Arabic pure from these words which are described asØ¯Ø®ÙŠÙ„ dakhil (literally meaning strange and outsider). Very few studies have been done on exploring the ways English loanwords are used in Saudi Colloquial Arabic (SCA) and the relationship between the use of English loanwords and some sociolinguistic variables such as sex, age, geographic location, and education. In the face of this, this article is concerned with exploring the relationship between sex and the use of English loanwords in Saudi Colloquial Arabic (SCA). In order to do this, the study is based on a corpus of English loanwords in Saudi Colloquial Arabic (SCA) with the purpose of investigating the frequency of English loanwords in the speeches of male and female speakers and describing the morphological adaptations used by male and female speakers. Results indicate that there are significant differences between Saudi male and female speakers in the use of English loanwords in terms of frequency, topics, and morphological adaptations. The sex or gender of the speaker is an important factor in determining the frequency, distribution, and the morphological adaptations of English loanwords in SCA.